Egg-based nutrient delivery system: advances in omega-3, antioxidant, and micronutrient enrichment - Ma, Cui; Azad, Md. Abul Kalam; Yu, Xiaoyue; Sun, Jing; Zhang, Hao; Pi, Jinsong; Wu, Yan (Frontiers in Nutrition, 2026)
Eggs are nutrient-dense, animal-derived foods with significant health-promoting properties. Beyond providing high-quality protein, their unique structure and balanced nutrient matrix make them ideal carriers for omega-3 polyunsaturated fatty acids, antioxidants, and essential micronutrients. This review summarizes current strategies for egg fortification, focusing on nutrient deposition mechanisms, bioavailability, and functional outcomes. We integrate metabolic transport pathways, including intestinal absorption, hepatic processing, lipoprotein assembly, and yolk deposition, to elucidate how nutrients are efficiently incorporated. This work demonstrates how targeted enrichment can enhance egg nutritional value and support preventive nutrition. Understanding nutrient incorporation provides practical guidance for poultry management, feed formulation, and the production of functional eggs, positioning them as a natural and effective dietary delivery system. By adopting a mechanistic and strategy-oriented perspective, we highlight the potential of next-generation functional eggs as effective vehicles for improving nutrient intake and advancing preventive and precision nutrition.